Alterations in Intestinal Microbiota Composition in Mice Treated With Vitamin D3 or Cathelicidin - Jiang, Yu; Wan, Yue; Li, Jing; Zhao, Yueshui; Ma, Yongshun; Yu, Jing; Yuan, Donghong; Xiang, Shixin; Du, Fukuan; Wu, Xu; Li, Mingxing; Chen, Yu; et al. (Frontiers in Oncology, 2021)
Gut microbiota is a complex aggregation of microbial organisms, which offers diverse protective benefits to the host. Dysbiosis of intestinal microbiota is frequently associated with many diseases. Vitamin D3 (VD), which was originally associated with bone health, also possesses antimicrobial activities and can act through antimicrobial peptide. Cathelicidin is a type of antimicrobial peptide in host to maintain the balance of gut microbiome. Our current study sought to evaluate the protective effect of VD and cathelicidin in mice intestines by administration of VD or mCRAMP-encoding L. lactis. We herein provided a comprehensive profile of the impact of VD and mCRAMP on gut microbiota using 16S rRNA sequencing, followed by bioinformatics and statistical analysis. Our results revealed an increased richness of bacterial community in mice intestines due to VD administration. Moreover, we showed a beneficial effect of VD and mCRAMP by enhancing the colonization of bacterial taxa that are associated with protective effects to the host but repressing the propagation of bacterial taxa that are associated with harmful effects to the host. Various metabolic pathways related to amino acid and lipid metabolism were affected in this process. We further established a bacterial panel as a reliable biomarker to evaluate the efficacy of remodeling the mice gut microbiota by VD and mCRAMP administration. The uncovered effects will deepen the comprehension about the antibacterial mechanisms of VD and mCRAMP and provide new insights for therapeutic implication of them.